Antes de la respuesta, la comprensión de la pregunta: ¿Es posible una ecología hoy?. (2021)
This article proposes understanding horizons to assume the question of a today’s ecology. Therefore realizes a basic description of science as a remarkable speech, which focuses on the measurable (positive) content nature (environment) has. The current article criticizes this scientific vision, and attributes it as well, a big part on the misunderstood issue about ecology. Un the other hand, it pretends to go deeper in the approach to the inquiring: ¿is it possible an ecology nowadays? Through a brief way over some philosophical questions, a speech word puzzle and a contract. Finally, it gets through an adequate thorough on the caused contradictions because of the ecological responsibility. There must be assumed emphatically as an ethical comprehension, as long as this precedes and contains any rational-kind judgment that states an appropriate action. It is stated that from philosophy, is where that sort of comprehension can light rigorously a sharp answer to this inquiring in order to a today’s ecology.